Pediatric Case Series with Early-Onset Dystonia: Clinical Clues of Inherited Manganese Transporter Defects - Hopurcuoglu, Duhan; Zubarioglu, Tanyel; Akgun, Abdurrahman; Kiykim, Ertugrul; Yalcinkaya, Cengiz; Iscan, Akin; Aktuglu-Zeybek, Ayse C. (Wolters Kluwer Medknow Publications, 2026)
Inherited manganese transporter defects are rare but treatable inborn errors of metabolism, typically presenting with early-onset dystonia and characteristic magnetic resonance imaging (MRI) findings. This case series included three pediatric patients: two with hypermanganesemia with dystonia type 1 (HMNDYT1) and one with type 2 (HMNDYT2). All showed early dystonia, gait disturbances, and speech difficulties. MRI revealed T1-weighted hyperintensities and T2-weighted hypointensities in the globus pallidus and substantia nigra. In HMNDYT1 cases, additional involvement of the dentate nuclei and midbrain was observed. Polycythemia was present in HMNDYT1 patients, while liver involvement was mild and limited to hyperbilirubinemia. All patients received chelation therapy with disodium calcium edetate (Na(2)CaEDTA), resulting in clinical stabilization and mild motor improvement in one case, although manganese levels remained elevated. These findings highlight the importance of including manganese transporter defects in the differential diagnosis of early-onset dystonia. Early recognition is essential for effective treatment.
Keywords: Hypermanganesemia; dystonia; disodium calcium edetate; magnetic resonance imaging; basal ganglia